2022
DOI: 10.1039/d2ra03983d
|View full text |Cite
|
Sign up to set email alerts
|

Effect of non-resonant background on the extraction of Raman signals from CARS spectra using deep neural networks

Abstract: Typical schematic of the CNN model architecture trained with CARS data generated from different non resonant backgrounds. The input is a CARS spectrum and the output is a Raman spectrum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 55 publications
0
16
0
Order By: Relevance
“…The CARS spectrum simulation procedure can be found in our previous work. 35 The simulation parameter details are presented in Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The CARS spectrum simulation procedure can be found in our previous work. 35 The simulation parameter details are presented in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…42 So, we have directly retrained it by utilizing their code without modifying any of its model parameters. In the case of the CNN, the trained model weights are directly taken from our previous work 35 and can be accessed from here. 43 Houhou et al have reported the LSTM model, but the trained weights and the respective codes are not openly available.…”
Section: Deep Learning Modelsmentioning
confidence: 99%
See 3 more Smart Citations